PENGARUH TINGKAT KESEJAHTERAAN, KEPUASAN KERJA, DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN AROMA SPA, SANUR DENPASAR - Hogantara, Andana; Sintaasih, Desak Ketut (E-Jurnal Manajemen, 2015)
The purpose of this study was to determine the effect of the level of well-being, job satisfaction, and organizational commitment to employee performance Aroma Spa, Sanur Denpasar. Respondents of this study were all employees of Aroma Spa, Sanur many as 40 people. The data analysis technique used is multiple linear regression analysis. The study states that the level of well-being, job satisfaction and organizational commitment simultaneously significant effect on employee performance. The level of well-being, job satisfaction and organizational commitment partially also positive and significant effect on employee performance. Finally, organizational commitment is a dominant variable on the performance of employees at Aroma Spa Sanur Denpasar.
Keywords: Tingkat Kesejahteraan; Kepuasan Kerja; Komitmen Organisasi; Kinerja Karyawan